2000
DOI: 10.1063/1.1308064
|View full text |Cite
|
Sign up to set email alerts
|

Giant capacitance effect and physical model of nano crystalline CuO–BaTiO3 semiconductor as a CO2 gas sensor

Abstract: A CO2 sensor made of nano crystalline CuO–BaTiO3 semiconductor, which has a giant capacitance effect, is designed based on the principle of the physical effect in the nano cluster. After an experimental investigation of its microstructure, the correlation between the quantum size effect and the giant capacitance effect is suggested. The characteristic physical quantities relating to the giant capacitance effect of the sensor are studied systematically with the aid of a gas detector. The quantum size effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The properties of BaTiO 3 -CuO as a carbon dioxide thermoactivated sensing material have been previously investigated [14][15][16][17][18][19][20][21][22][23][24][25][26]. Thick-film technology and sintering are used to synthesize the material in most of the research carried out [20][21][22][23][24][25][26], while thin-film technology is only reported by the authors [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of BaTiO 3 -CuO as a carbon dioxide thermoactivated sensing material have been previously investigated [14][15][16][17][18][19][20][21][22][23][24][25][26]. Thick-film technology and sintering are used to synthesize the material in most of the research carried out [20][21][22][23][24][25][26], while thin-film technology is only reported by the authors [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Thick-film technology and sintering are used to synthesize the material in most of the research carried out [20][21][22][23][24][25][26], while thin-film technology is only reported by the authors [14][15][16][17][18][19]. The BaTiO 3 -CuO sensing films obtained by different technologies show different physical-chemical behaviour under different carbon dioxide concentrations and operation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the properties of BaTiO 3 -CuO as a sensitive material under carbon dioxide atmospheres have been investigated [1][2][3][4][5][6][7][8][9][10]. Thick film technology and sintering are used to synthesize the material in most of the research works [4][5][6][7][8][9][10], while thin film technology is only reported by the authors [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Thick film technology and sintering are used to synthesize the material in most of the research works [4][5][6][7][8][9][10], while thin film technology is only reported by the authors [1][2][3]. Thin film technology shows advantages in terms of controllability of the process parameters and material properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A variety of approaches (e.g., mixed oxide, mixed salt, sol-gel, polymeric precursor, hydrothermal, microemulsion, mechanochemical, and combustion syntheses) have been used to synthesize BaTiO 3 powders with fine particle and crystal sizes. [9][10][11][12][13][14][15][16][17][18][19] Nanocrystalline barium titanate-based ceramics have exhibited relatively high room-temperature dielectric constants that are temperature-and voltage-stable for integrated capacitors, 20,21 high sensitivity to water vapor and carbon dioxide for gas sensors, [22][23][24] and enhanced response of fluorescence to temperature changes for real-time temperature monitoring. 25 The worldwide interest in nanoscale ferroelectric devices has also led to the recent syntheses of BaTiO 3 nanowires, 26 nanorods, 27 nanoshell tubes, 28 and nanoshell spheres.…”
mentioning
confidence: 99%